2002
DOI: 10.1080/10473289.2002.10470785
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship between Acid Rain and Cloud Type

Abstract: Spanish European Monitoring and Evaluation Programme (EMEP) stations were selected to relate acid rain episodes with the meteorological structure that caused the rainfall during a 5-year period. A principal component analysis (PCA) was used to determine the origin of major ions (SO4(2-), NO3-, Cl-, Ca2+, K+, Mg2+, and Na+) in the rainwater. In addition, the meteorological origin of the rain was identified. Previous works suggested a relationship between acid rain and storm convective clouds. However, statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…For instance, several studies (e.g. Dawson, 1978;Cana-Cascalar, 2002) analysed the relationship between ionic concentrations and storm type. The latter researchers found that short-lived convective conditions over Spain may cause rain to be more acidic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, several studies (e.g. Dawson, 1978;Cana-Cascalar, 2002) analysed the relationship between ionic concentrations and storm type. The latter researchers found that short-lived convective conditions over Spain may cause rain to be more acidic.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include time-series analyses using linear and nonlinear regression techniques (Buda and DeWalle, 2002;Seto et al, 2002;Nickerson and Madsen, 2005), cluster and principalcomponent analyses (e.g. Dorling et al, 1992;Cana-Cascalar, 2002), and spatial-pattern analyses of atmospheric circulation (Davies et al, 1991;Yarnal, 1991Yarnal, , 1993Dorling et al, 1992;Lamb, 2003, 2005). Typical studies employ the ionic concentrations, rather than the deposition flux itself, because precipitation composition is closely linked to the concentrations of precursors in air (Engelman, 1971;Davis et al, 1997;Hicks, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…5 ) followed by the earliest smog advisory ever 1ssued dunng the normal smog season in April , 2005. As shown in Table 1, there has been an increase in smog advisories since 2002 [12), [13) , [14) and [15]. Since 1999, each air quality study completed states that the air quality in Ontario is improving [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 1, there has been an increase in smog advisories since 2002 [12), [13) , [14) and [15]. Since 1999, each air quality study completed states that the air quality in Ontario is improving [12][13][14][15][16][17][18]. In 2005, the Ontario Medical Association (OMA) announced air pollution costs were estimated to be $507,000,000 in direct health care costs [1 ].…”
Section: Introductionmentioning
confidence: 99%
“…5 ) followed by the earliest smog advisory ever 1ssued dunng the normal smog season in April , 2005. As shown in Table 1, there has been an increase in smog advisories since 2002 [12), [13) , [14) and [15]. Since 1999, each air quality study completed states that the air quality in Ontario is improving [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%